EVALUATION OF THE IMPLEMENTATION OF THE PURWOREJO DISTRICT GOVERNMENT INTERNAL CONTROL SYSTEM (SPIP) BASED ON ISO 31000: 2018 RISK MANAGEMENT GUIDELINES - Saffela, Nurika Indah; Rusmana, Oman (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
Risk management in local government is very important as an effort to maximize the achievement of organizational goals. This article aims to evaluate the implementation of the Government Internal Control System (SPIP) in Purworejo Regency based on the principles and framework of risk management ISO 31000: 2018 and the OECD Best Practice Principles for Regulatory Policy framework. The evaluation was conducted through document analysis of Purworejo's SPIP guidelines and comparators from ISO.The results of the study show that the implementation of SPIP has adopted some of the ISO 31000 principles structurally, but still faces obstacles in the aspects of integration, monitoring, and stakeholder involvement. Purworejo's SPIP shows that formal documents, such as Regent Regulations and Decree on the formation of an internal control team, are available. However, the integration has not touched all levels of the organization evenly. Recommendations for improvement include increasing the capacity of human resources, digitizing the risk information system, and establishing standardized key risk indicators.